2015
DOI: 10.1080/0972060x.2015.1010597
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oil Components, Microelement Contents and Antioxidant Effects ofNepeta italicaL. andAchillea filipendulinaLAM.

Abstract: The genus Nepeta (Lamiaceae) and Achillea (Asteraceae) are widely distributed in Turkey.In this study, the essential oils of Nepeta italica L. and Achillea filipendulina LAM. collected from Dicle district in Diyarbakir province in the Southeast Anatolia and from Hakkari province in East Anatolia of Turkey, were obtained by hydrodistillation of the aerial parts. The essential oils from Nepeta italica and Achillea filipendulina obtained by hydrodistillation were analyzed by gas chromatography-mass spectrometry G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Hasimi et al . also the essential oil of the A. filipendulina collected from Turkey, and found that 1,8‐cineole (22.9 %), 2,7‐dimethylocta‐3,6‐dien‐2‐ol (also that is maybe santolina alcohol (21.9 %), borneol (8.1 %), isoterpineolene (6.1 %), cis ‐ p ‐menth‐2,8‐dienol (7.9 %), bornyl acetate (5.0 %), p ‐cymene (2.6 %), and α ‐terpinene (2.4 %) were as main constituents . In another study, the chemical composition of eight Achillea species collected from Salafchegan (Markazi province, Iran) were studied, and santolina alcohol (27.1 %), bornyl acetate (15.86 %), germacrene‐D (19.82 %), borneol (7.8 %), and 1,8‐cineol (2.68 %) were the major components .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hasimi et al . also the essential oil of the A. filipendulina collected from Turkey, and found that 1,8‐cineole (22.9 %), 2,7‐dimethylocta‐3,6‐dien‐2‐ol (also that is maybe santolina alcohol (21.9 %), borneol (8.1 %), isoterpineolene (6.1 %), cis ‐ p ‐menth‐2,8‐dienol (7.9 %), bornyl acetate (5.0 %), p ‐cymene (2.6 %), and α ‐terpinene (2.4 %) were as main constituents . In another study, the chemical composition of eight Achillea species collected from Salafchegan (Markazi province, Iran) were studied, and santolina alcohol (27.1 %), bornyl acetate (15.86 %), germacrene‐D (19.82 %), borneol (7.8 %), and 1,8‐cineol (2.68 %) were the major components .…”
Section: Resultsmentioning
confidence: 99%
“…There are also some components such as cis ‐chrysanthenyl acetate that is only present in the stem of this plant. Moreover, there are almost no major components present in all three segments of the plant . Several studies have shown that santolina alcohol, carvacrol, 1,8‐cineole, and borneol exhibited antimicrobial activates against bacteria, with two latter also demonstrating synergistic effects .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the mineral element contents of leaves of Scutellaria luteo‐caerulea from Iran were developed, whereas the organic chemical compositions of its essential oil were determined by GC‐MS . Using hydro‐distillation, the extracted essential oil from Nepeta italica and Achillea filipendulina were analysed by GC‐MS, and the microelements of the plants were determined by induced coupled plasma optical emission spectrometry . Also, GC‐MS was used for estimation of the organic chemical composition of essential oils extracted from Algerian Inula viscosa leaves, Stevia rebaudiana Bertoni leaves grown in Bangladesh, and Zanthoxylum genus in China .…”
Section: Introductionmentioning
confidence: 99%
“…They are used for ulcer, appetizing, carminative, diuretic and against fleas as insecticidal [4][5][6][7] A. millefolium reviewed by German Commission E advert to its astringent, cholerethic, antibacterial, antispasmodic effects [8]. In literature survey, the essential oil of Achillea species showed antioxidant [9][10][11], antimicrobial and antifungal [12][13][14][15][16], antimelanogenesis [17], antiinflammatory and for healing [18,19], cytotoxic and insecticidal activities [20][21][22].…”
Section: Introductionmentioning
confidence: 99%